Clinical diagnosis of Alzheimer's disease: recommendations of the International Working Group. Issue 6 (June 2021) - Dubois, Bruno; Villain, Nicolas; Frisoni, Giovanni B; Rabinovici, Gil D; Sabbagh, Marwan; Cappa, Stefano; Bejanin, Alexandre; Bombois, Stéphanie; Epelbaum, Stéphane; Teichmann, Marc; Habert, Marie-Odile; Nordberg, Agneta; et al.
Summary: In 2018, the US National Institute on Aging and the Alzheimer's Association proposed a purely biological definition of Alzheimer's disease that relies on biomarkers. Although the intended use of this framework was for research purposes, it has engendered debate and challenges regarding its use in everyday clinical practice. For instance, cognitively unimpaired individuals can have biomarker evidence of both amyloid β and tau pathology but will often not develop clinical manifestations in their lifetime. Furthermore, a positive Alzheimer's disease pattern of biomarkers can be observed in other brain diseases in which Alzheimer's disease pathology is present as a comorbidity. In this Personal View, the International Working Group presents what we consider to be the current limitations of biomarkers in the diagnosis of Alzheimer's disease and, on the basis of this evidence, we propose recommendations for how biomarkers should and should not be used for diagnosing Alzheimer's disease in a clinical setting. We recommend that Alzheimer's disease diagnosis be restricted to people who have positive biomarkers together with specific Alzheimer's disease phenotypes, whereas biomarker-positive cognitively unimpaired individuals should be considered only at-risk for progression to Alzheimer's disease.